2010
DOI: 10.1358/dnp.2010.23.4.1453629
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage migration inhibitory factor (MIF): A promising biomarker

Abstract: Macrophage migration inhibitory (MIF) factor is an immunoregulatory cytokine whose effect on arresting random immune cell movement was recognized several decades ago. Despite its historic name, MIF also has a direct chemokine-like function and promotes cell recruitment. Multiple clinical studies have pointed to the utility of MIF as a biomarker for different diseases that have an inflammatory component; these include systemic infections and sepsis, autoimmune diseases, cancer, and metabolic disorders such as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
176
2
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(185 citation statements)
references
References 101 publications
4
176
2
3
Order By: Relevance
“…In the presence of high concentrations of MIF, this is suppressed by inhibiting p-53 dependent apoptosis, giving rise to an extended immune response with TNF-α and IL-1β production, leading to further MIF release (26). In the pathogenesis of AAV, priming of neutrophils by cytokines is a key feature (2), and high levels of MIF could contribute to this (8,11). MIF and GC seems to have reciprocal effects on the immune system and, unlike other cytokines, low doses of GC seem to be able to induce MIF, at least in animal models (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the presence of high concentrations of MIF, this is suppressed by inhibiting p-53 dependent apoptosis, giving rise to an extended immune response with TNF-α and IL-1β production, leading to further MIF release (26). In the pathogenesis of AAV, priming of neutrophils by cytokines is a key feature (2), and high levels of MIF could contribute to this (8,11). MIF and GC seems to have reciprocal effects on the immune system and, unlike other cytokines, low doses of GC seem to be able to induce MIF, at least in animal models (18).…”
Section: Discussionmentioning
confidence: 99%
“…MIF is central to the innate immune response system with an upstream role in the inflammatory cascade, promoting the release of other inflammatory cytokines including TNF-α and IL-1β. Furthermore, MIF has a chemokinelike function and promotes recruitment of leukocytes in general and neutrophils specifically into infectious and inflammatory sites (8,9). Previously, MIF has been demonstrated to play a role in sepsis (10,11), autoimmune disease (12)(13)(14), chronic kidney disease (15), pulmonary hypertension (16) and cardiovascular disease (17).…”
mentioning
confidence: 99%
“…It is involved in immunological and inflammatory diseases [9,10] such as chronic diseases including bowel disease [11], obesity [12,13], and diabetes [14]. More recently, MIF was proposed as a diagnostic biomarker for autoimmune diseases such as diabetes [15].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that genetic factors play an important role in GDM occurrence (Zhang et al, 2013). Macrophage migration inhibitory factor (MIF) is a protein that can function as a cytokine, hormone, or enzyme and exhibits a variety of biological activities, playing an important role in inflammation and immunity (Grieb et al, 2010). Previous studies have shown that MIF is related to the occurrence of obesity and insulin resistance syndromes (Finucane et al, 2012), and MIF gene polymorphisms have been correlated with GDM and metabolic syndromes (Aslani et al, 2011).…”
Section: Introductionmentioning
confidence: 99%